Systematic cell placement in quantum‐dot cellular automata embedding underlying regular clocking circuit. Issue 2 (28th January 2021) - Bhowmik, Dhrubajyoti; Pal, Jayanta; Goswami, Mrinal; Sen, Pinaki; Saha, Apu Kumar; Sen, Bibhash
Abstract: Quantum‐dot cellular automata (QCA) is gaining worldwide popularity due to its higher device concentration, lower power indulgence, and better switching speed. The information flows in QCA with the polarization state defined by the placement of electrons instead of current flow. The cell interaction principle under the influence of the clocking zone controls the cell placement during QCA circuit design. Most of the designs reported so far used random cell placement, which has no fabricating sense. Moreover, it is equally important for a cell placement algorithm to follow a realistic, regular underlying clocking scheme to maintain proper routing channels. In this regard, a systematic cell placement for the combinational logic circuit in QCA is proposed using the widely accepted underlying regular clocking scheme, universal, scalable and efficient (USE). The proposed method traverses all possible paths of a combinational logic circuit from output to input to build the desired circuit generating the automatic cell layout. A grid of clock zone of USE clock scheme is considered in the initial layout driving different paths of the circuit and finally evolves as the desired circuit. The generated automatic QCA layouts are competitive in occupied area, delay, and its cell count, which advocates the significance of such a scheme.